1999
DOI: 10.1246/cl.1999.659
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxy Group-Directed Homolytic Hydrostannylation of Alkenols with Dibutylchlorostannane

Abstract: In homolytic hydrostannylation of allyl alcohol 1a or homoallyl alcohol 1b, dibutylchlorostannane (Bu2ClSnH) exhibited a much higher reactivity than tributylstannane (Bu3SnH). Competitive reaction of 1a  vs. 1-octene with Bu2ClSnH led to the selective formation of γ-stannylated alcohol 3a. Hydrostannylation of 1,5-hexadien-3-ol (8) with Bu2ClSnH favored 1-stannylated product 9 over 6-stannylated product 10, while the use of Bu3SnH decreased the regioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Previously, we have reported that dibutylchlorostannane (Bu 2 SnClH) 6 exhibits high chemoselectivity toward homolytic hydrostannylation of allyl and homoallyl alcohols . The chemoselectivity is attributable to the coordination of the hydroxy group to the Lewis acidic tin center in the β-stannylalkyl radical intermediate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have reported that dibutylchlorostannane (Bu 2 SnClH) 6 exhibits high chemoselectivity toward homolytic hydrostannylation of allyl and homoallyl alcohols . The chemoselectivity is attributable to the coordination of the hydroxy group to the Lewis acidic tin center in the β-stannylalkyl radical intermediate.…”
mentioning
confidence: 99%
“…5 Previously, we have reported that dibutylchlorostannane (Bu 2 SnClH) 6 exhibits high chemoselectivity toward homolytic hydrostannylation of allyl and homoallyl alcohols. 7 The chemoselectivity is attributable to the coordination of the hydroxy group to the Lewis acidic tin center in the β-stannylalkyl radical intermediate. This deduction prompted us to utilize such an intramolecular interaction for regio-and stereoselective hydrostannylation of alkynes bearing a polar functional group.…”
mentioning
confidence: 99%
“…3 We have recently reported highly regio-and stereoselective hydrostannylation of g-unsubstituted propargyl alcohols with Bu 2 SnClH. [7][8][9] Unfortunately, this method involves the Et 3 B-initiated reaction at low temperatures for the purpose of achieving both high levels of regiocontrol and high reaction efficiency. 10 Bu 2 SnClH reacted smoothly with these alkynes at room temperature even in the absence of Et 3 B; however, there is some room for improvement of the regioselectivity.…”
mentioning
confidence: 99%
“…The 119 Sn signal of Bu 2 SnClH (0.3 mmol in 0.6 mL of THF-d8 ) appeared at d = -30.9 ppm (vs Me 4 Sn). 15 Its 1 H NMR and 13 C NMR analyses revealed the coupling constants of tin with the adjacent proton and carbon [ 1 J ( 119 Sn-1 H) = 2208 Hz, 1 J ( 119 Sn-13 C) = 463 Hz].…”
mentioning
confidence: 99%
“…Reports of hydrostannylation and hydrosilylation of alkenes via a radical mechanism are limited in organic synthesis. Hydrostannylation of alkenes via a radical intermediate often gives low yields because the addition of stannyl radicals is reversible and the equilibrium favors the starting materials …”
mentioning
confidence: 99%